Rome and Persia : the seven hundred year rivalry - Goldsworthy, Adrian Keith (Basic Books, 2023)
"The relationship between the Roman Empire and its rival, the Parthian-Persian Empire, has long been viewed as bloody, hostile, and destructive. In fact, the truth is more complex. For more than seven hundred years, the Romans lived side by side by their eastern neighbors, sometimes at war, more often at peace, almost always trading with each other to their mutual benefit. The Roman Empire was wealthier and larger than the Persian Empire and its predecessor, the Parthian Empire, but all three enjoyed a level of sophistication unprecedented in history. The bitter rivals had no choice but to view one another with suspicion as well as respect. The empires tread a tenuous peace-until, following the Arab Conquests, Persia collapsed and Rome violently contracted. Covering seven centuries of imperial competition, Rome and Persia offers the definitive history of the epic rivalry between the ancient world's superpowers. Drawing on extensive research, historian Adrian Goldsworthy traces how the empires clashed as they co-evolved, from first-century diplomatic misunderstandings between the Roman Republic and Parthia, through centuries of bitter assaults on both sides under dozens of leaders, to the Sassanid clan's seizure of Persian power from the Parthian dynasty in the third century, to a fifth-century return to wary peace between nations as the strength of both sides fluctuated. Across the ages, trade between Rome and Persia helped enrich both empires, and each side maintained active, if tense, diplomatic relations with the other. Even as Romans tried to conquer all their other enemies, they grudgingly respected Persia and never tried to permanently neutralize the empire; Persians also restrained themselves when caught in conflict with Rome. Only with the sudden onset of a titanic, exhausting, and ultimately futile war launched by the last great Sasanian king in the 7th century did the two empires overstretch themselves and severely weaken one another. In the wake of the devastating conflict, ascendant Arab armies easily conquered Persia, sweeping away the Sasanians, and left the Roman Empire as a shadow of its former self. Authoritative and epic in scope, this completely reshapes our understanding of the ancient world's two superpowers, revealing the fascinating history of Rome and Persia's rivalry and the empires' rich legacies"--